Recent research on the bioactivity of polyphenols derived from edible fungi and their potential in chronic disease prevention - Wenbin Yu; Yufei Zhang; Yi Lu; Zhiwei Ouyang; Jiahua Peng; Yayi Tu; Bin He (Journal of Functional Foods)
Chronic diseases pose a significant threat to global public health, demanding innovative preventive and therapeutic strategies. Recent research has brought to light the nutritional and bioactive properties of edible fungi, with a particular focus on the bioactivity of mushroom polyphenols. These compounds have shown promising antioxidant, anti-inflammatory, and anticancer effects, which hold substantial implications for human health. This article provides a comprehensive review of the classification, bioavailability, and bioactive functions of polyphenols derived from edible fungi, with an emphasis on the role of mushroom polyphenols in the prevention of chronic diseases. The integration of these findings with ongoing research on synergistic effects and optimal edible strategies will be crucial for advancing our understanding and enhancing the development of targeted nutritional interventions. In conclusion, the exploration of polyphenols from edible fungi presents a promising frontier for developing novel preventive and therapeutic approaches to combat chronic diseases.